Pengaruh Pemikiran Tokoh Pembaharuan Muhammad Abduh dan Rasyid Ridha terhadap Perkembangan Pendidikan Islam di Indonesia - Moh Ngizudin; Ilham Ilham; Rina Setyaningsih; Agus Rojul Solihin; Rohimin Rohimin; Khalishah Sukma Syam (Lembaga Pengembangan Kinerja Dosen, 2025)
This research analyses the influence of the reformist thoughts of Rashid Ridha and Muhammad Abduh on the development of Islamic education in Indonesia. Using a descriptive qualitative method with a literature study approach, this research examines how the modernist ideas of the two figures shaped the transformation of the paradigm of Islamic education in Indonesia. The findings show that the thoughts of Rashid Ridha and Muhammad Abduh significantly influenced the development of modern Islamic educational institutions, curriculum integration, and pedagogical approaches in Indonesia. Their reformist ideas contributed to the establishment of modern Islamic schools, the integration of religious and general sciences, and the development of rational Islamic thought. This research contributes to understanding the historical roots of Islamic education modernisation in Indonesia and its relevance to contemporary education development.